1997
DOI: 10.1046/j.1464-410x.1997.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, double‐blind study comparing lignocaine gel and plain lubricating gel in relieving pain during flexible cystoscopy

Abstract: Objective To determine the optimum duration for the 25 min. The patients' discomfort was recorded using a 4-point descriptive pain scale and a 100 mm nonretention of 2% lignocaine gel intraurethrally as an anaesthetic for flexible cystoscopy in men.graphical visual analogue scale. Results In the first study, those patients receiving lignoPatients and methods A prospective, randomized, double-blind, placebo-controlled trial was conducted caine gel for 25 min experienced significantly less pain than the other th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 1 publication
3
53
0
4
Order By: Relevance
“…Herr and Schneide's study showed no difference in pain relief between cystoscopy performed immediately after lidocaine gel instillation and after 15 min delay [20]. Choong and associates further stated that lidocaine gel was effective in decreasing pain when cystoscopy is performed after 15 min or longer of the instillation [21]. Other previous studies indicated that effective local anesthesia and lubrication of lidocaine gel or plain petrolatum instillation should be done by remaining the gel in the urethra for 10 to 15 minutes before cystoscopy [21,22].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Herr and Schneide's study showed no difference in pain relief between cystoscopy performed immediately after lidocaine gel instillation and after 15 min delay [20]. Choong and associates further stated that lidocaine gel was effective in decreasing pain when cystoscopy is performed after 15 min or longer of the instillation [21]. Other previous studies indicated that effective local anesthesia and lubrication of lidocaine gel or plain petrolatum instillation should be done by remaining the gel in the urethra for 10 to 15 minutes before cystoscopy [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…Choong and associates further stated that lidocaine gel was effective in decreasing pain when cystoscopy is performed after 15 min or longer of the instillation [21]. Other previous studies indicated that effective local anesthesia and lubrication of lidocaine gel or plain petrolatum instillation should be done by remaining the gel in the urethra for 10 to 15 minutes before cystoscopy [21,22]. Currently, it is a common practice in busy outpatient clinics to perform cystoscopy within 5 minutes after the intraurethral instillation of lidocaine gel [23].…”
Section: Discussionmentioning
confidence: 99%
“…There has also been a study showing the opposite result from our study. Choong et al [10] back in 1997 found that the most adequate time of 20 ml of 2% lidocaine gel exposures to urethra may be 15 minutes; they assert that time is needed for the anesthetic ingredients to infiltrate the urothelium. We believe that the discrepancy may be due to the differences in the volume of the injected lidocaine gel.…”
Section: Discussionmentioning
confidence: 99%
“…Choong et al . [12] first reported a significant reduction in pain during flexible cystoscopy when 20 mL of 2% lignocaine gel was left in the urethra for 15 min compared to 5 min. However, multiple authors have since failed to replicate these results [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%